Application of Theory of Planned Behavior in Predicting Factors of Substance Abuse in Adolescents - Saeid Bashirian; Alireza Haidarnia; Hamid Allahverdipour; Ebrahim Hajizadeh (Fasa University of Medical Sciences, 2012)
Background and Objective: Adolescence is the most critical period of life as regards commencing drug abuse. The social cost and damage caused by drug abuse in adolescence are enormous, necessitating interventional programs to prevent this behavior. The theory of planned behavior (TPB) is perhaps the most influential theory for the prediction of social and health behaviors such as drug abuse.Materials and Methods: In this descriptive analytical study, samples were collected from male students in four high schools in different regions of Hamedan. The survey was carried out via random cluster sampling of 650 students. Data were collected using the standard self-report questionnaires and were analyzed using SPSS16, chi-squared test, correlation coefficient, and logistic regression analysis.Results: Among the adolescents participating in this study, 11.1% had the experience of cigarette smoking, 3.4% had the experience of drug abuse, and 12% had the experience of intention to abuse drugs. There was a significant relationship between drug abuse and the following variables: smoking experience (p value =0.001, OR=27.238) having drug user parents (p value =0.001, OR=8.630) having friends who had experienced drug abuse (p value =0.001, OR=11.060) having best friends who had experienced drug abuse (p value = 0.001, OR=11.931) family with drug abuse (p value = 0.001, OR=4.311) and having a sibling who abused drugs (p value=0.001, OR=15.815). According to the logistic regression analysis, attitude, subjective norms, and perceived behavior control were the most influential predictors of intention to abuse drugs.Conclusion: The use of TPB is beneficial in the predicting and planning for high-risk behaviors. TPB can be used for planning and implementing drug abuse prevention programs in adolescents.